Can the global drone revolution make agriculture more sustainable? Rapid growth in drone use is upending expectations but also inducing trade-offs - Belton, Ben; Baldiga, Leo; Justice, Scott; Minten, Bart; Narayanan, Sudha; Reardon, Thomas (American Association for the Advancement of Science, 2025)
Use of drones has increased considerably over the past decade, reshaping activities as diverse as warfare, entertainment, delivery services, and disease control. One of the most consequential uses of drones—in agriculture—has taken off globally within only the past 5 years. This is upending expectations and may help to reconcile a fundamental sustainability dilemma—how to produce more food by using fewer inputs—but is also inducing trade-offs. This rapid change has been largely unnoticed by researchers outside of the specialized technical worlds of aeronautical engineering and precision agriculture. Little academic attention has been paid to the use of agricultural drones beyond the laboratory or trial plot. Evidence of the extent and effects of drones’ real-world use is partial and fragmentary. We explored evidence and hypotheses about global agricultural drone diffusion and its implications for sustainability and set out an agenda for future policy and science.